Predictive Factors for Acute Postoperative Pain After Open Radical Gastrectomy for Gastric Cancer - Xie, Han; Wei, Jingxuan; Ma, Zhengliang; Ge, Weihong (Frontiers in Public Health, 2022)
Background Pain has become an important factor in evaluating patients' quality of life and clinical treatment. For gastric cancer (GC) patients, open radical gastrectomy (OG) causes significant trauma to the body, increases patients' pain after operation, and delays early recovery. The aim of this study was to investigate the predictive factors of acute pain after OG within postoperative 72 h. Methods From March 2020 to September 2021, 307 patients who underwent OG were included in the study in Nanjing Drum Tower Hospital. The predictors included demographic predictors, pathological data, surgical predictors, and intraoperative predictors. The pain scores at 12, 24, 48, and 72 h after operation were evaluated by numeric rating scale (NRS). The predictors of acute pain were determined by univariate and multivariate analysis. Results The average pain score (NRS) of patients showed a downward trend over time within 72 h after OG. Multivariate analysis indicated that total gastrectomy (OR 1.823, 95% CI 1.094–3.040, P < 0.05), AJCC TNM stage (II) (OR.232, 95% CI 0.062–0.872, P < 0.05), AJCC TNM stage(III) (OR.185, 95% CI 0.049–0.698, P < 0.05), BMI (kg/m2) (OR 1.75, 95% CI 1.029–2.976, P < 0.05), distant metastasis (OR 3.054, 95% CI 1.019–9.155, P < 0.05), intraoperative transfusion (OR 2.246, 95% CI 1.267–3.982, P < 0.01) were significant predictive factors for acute pain after OG. Conclusion Reasonable postoperative acute pain control was the prerequisite for accelerating the postoperative rehabilitation of patients. In order to reduce the occurrence of excessive or insufficient analgesia, it was necessary for patients who underwent OG to formulate appropriate analgesics according to risk factors.